Zig-zag deformations of toric quiver gauge theories. Part I. Reflexive polytopes - Stefano Cremonesi; José Sá (Journal of High Energy Physics, 2024)
Abstract We study one-parameter families of U(1)2 preserving deformations relating pairs of toric quiver gauge theories on D-branes probing local toric (pseudo) del Pezzo surfaces. The superpotential deformations are defined by zig-zag paths in the brane tiling and are non-trivial in the chiral ring if the geometry has a non-isolated singularity. In the dual (p, q) web, the deformation is realized as a Hanany-Witten move that reverses a semi-infinite fivebrane. We use these deformations to find RG flows between 4d N $$ \mathcal{N} $$ = 1 SCFTs on D3-branes probing local toric (pseudo) del Pezzo surfaces of the same degree, and briefly comment on the interpretation for BPS quivers of rank one 5d SCFTs on S 1.